Depolymerizable semi-fluorinated polymers for sustainable functional materials. Issue 18 (13th April 2022) - Sathe, Devavrat; Zhou, Junfeng; Chen, Hanlin; Schrage, Briana R.; Yoon, Seiyoung; Wang, Zeyu; Ziegler, Christopher J.; Wang, Junpeng
Abstract : Chemically recyclable semi-fluorinated polymers are demonstrated for the first time, and the hydrophobicity, self-assembly, and post-polymerization functionalization of these polymers are explored. Abstract : Fluorinated polymers are important functional materials for a broad range of applications, but the recycling of current fluorinated polymers is challenging. We present the first example of semi-fluorinated polymers that can undergo chemical recycling to form the corresponding monomers under ambient conditions. Prepared through ring-opening metathesis polymerization of functionalized trans -cyclobutane fused cyclooctene ( t CBCO) monomers, these polymers show tunable glass transition temperatures (−2 °C to 88 °C), excellent thermal stability (decomposition onset temperatures >280 °C) and hydrophobicity (water contact angles >90°). The hydrophobicity of the semi-fluorinated polymers was further utilized in an amphiphilic diblock copolymer, which forms self-assembled micelles with a size of ∼88 nm in an aqueous solution. Finally, through an efficient, regioselective para -fluoro-thiol substitution reaction, post-polymerization functionalization of a polymer with a pentafluorophenyl imide substituent was achieved. The ease of preparation, functionalization, and recycling, along with the diverse thermomechanical properties and demonstrated hydrophobicity make the t CBCO-based depolymerizable semi-fluorinated polymers promising candidates for sustainable functional materials that can offer a solution to a circular economy.